Novel approach for reconstruction of the three-dimensional biliary system in decellularized liver scaffold using hepatocyte progenitors. - Kazuya Hirukawa; Hiroshi Yagi; Kohei Kuroda; Masafumi Watanabe; Kotaro Nishi; Shogo Nagata; Yuta Abe; Minoru Kitago; Shungo Adachi; Ryo Sudo; Yuko Kitagawa (PLoS ONE, 2024)
Reconstruction of the biliary system is indispensable for the regeneration of transplantable liver grafts. Here, we report the establishment of the first continuous three-dimensional biliary system scaffold for bile acid excretion using a novel method. We confirmed the preservation of the liver-derived extracellular matrix distribution in the scaffold. In addition, hepatocyte progenitors decellularized via the bile duct by slow-speed perfusion differentiated into hepatocyte- and cholangiocyte-like cells, mimicking hepatic cords and bile ducts, respectively. Furthermore, qRT-PCR demonstrated increased ALB, BSEP, and AQP8 expression, revealing bile canaliculi- and bile duct-specific genetic patterns. Therefore, we concluded that locally preserved extracellular matrices in the scaffold stimulated hepatic progenitors and provided efficient differentiation, as well as regeneration of a three-dimensional continuous biliary system from hepatic cords through bile ducts. These findings suggest that organ-derived scaffolds can be utilized for the efficient reconstruction of functional biliary systems.